Selective index of the publications in the journal Proceedings on Applied Botany, Genetics and Breeding dedicated to Nikolay Vavilov’s life, activities and scientific works - article Editorial (Труды по прикладной ботанике, генетике и селекции)
The present list shows the publications that appeared in the journal Proceedings on Applied Botany, Genetics and Breeding from 1912 to 2022. All of them were dedicated to the life, activities and scientific achievements of Nikolay Vavilov as well as to his contribution to the contemporary research trends. The main attention is focused on Vavilov as a researcher, founder and leader of VIR. Of course, the compilers presented only a fraction of the publications describing the versatile activities of this scientist of worldwide renown. Most of the papers were published by his disciples, associates and colleagues in the journal’s celebration issues to honor the memory of Nikolay Vavilov as a prominent Russian scientist. Besides, there are publications with Vavilov’s photos and other materials submitted by him as the leader and plant explorer of collecting missions to the authors of Proceedings on Applied Botany, Genetics and Breeding.